Collection of historical documents in relation with the Syriac Orthodox community in the late period of the Ottoman Empire - Bcheiry, Iskandar. (Piscataway, NJ)
vii, 118 sayfa
Keywords: “In the Ottoman Empire, Syriac communities kept their own baptismal books, marriage, funeral and other records and many of these can be found in various libraries, churches, monasteries in the West and East. The Syriac Garšūnī manuscript found in the Church of the Forty Martyrs in Mardin contains several lists of different subjects that go back to the late period of the Ottoman Empire. These lists, published here for the first time with annotations, are an important historical source for the social, economic, cultural and religious history of the Near East during the 19th century“ -- Yayıncı.